Flexible metal-organic frameworks - Schneemann, Andreas; Bon, Volodymyr; Schwedler, I.; Senkovska, Irena; Kaskel, Stefan; Fischer, R. A. (Chemical Society Reviews, 2014)
Advances in flexible and functional metal-organic frameworks (MOFs), also called soft porous crystals, are reviewed by covering the literature of the five years period 2009-2013 with reference to the early pertinent work since the late 1990s. Flexible MOFs combine the crystalline order of the underlying coordination network with cooperative structural transformability. These materials can respond to physical and chemical stimuli of various kinds in a tunable fashion by molecular design, which does not exist for other known solid-state materials. Among the fascinating properties are so-called breathing and swelling phenomena as a function of host-guest interactions. Phase transitions are triggered by guest adsorption/desorption, photochemical, thermal, and mechanical stimuli. Other important flexible properties of MOFs, such as linker rotation and sub-net sliding, which are not necessarily accompanied by crystallographic phase transitions, are briefly mentioned as well. Emphasis is given on reviewing the recent progress in application of in situ characterization techniques and the results of theoretical approaches to characterize and understand the breathing mechanisms and phase transitions. The flexible MOF systems, which are discussed, are categorized by the type of metal-nodes involved and how their coordination chemistry with the linker molecules controls the framework dynamics. Aspects of tailoring the flexible and responsive properties by the mixed component solid-solution concept are included, and as well examples of possible applications of flexible metal-organic frameworks for separation, catalysis, sensing, and biomedicine. This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-20